The Risk of Metachronous Advanced Neoplasia After Colonoscopy in Patients Aged 40–49 Years Compared With That in Patients Aged 50–59 Years. (12th August 2022) - Ma, Gene; Anderson, Meredith; Liu, Liyan; Li, Dan
Abstract : INTRODUCTION: This study investigated the risk of metachronous advanced neoplasia (AN) after colonoscopy in individuals aged 40–49 years compared with that in individuals aged 50–59 years. METHODS: A retrospective cohort study was performed among Kaiser Permanente Northern California members aged 40–59 years who had their first (index) colonoscopy in 2010–2013. Participants were followed up until death, disenrollment, AN on surveillance colonoscopy, or December 31, 2018. The risk for the development of AN was estimated using the Cox regression, adjusted for confounders. RESULTS: The study included 11, 374 patients (2, 396 aged 40–49 years and 8, 978 aged 50–59 years). When comparing the 40–49 years group with the 50–59 years group, AN was detected in 2.2% vs 4.4% ( P = 0.0003) on surveillance colonoscopy after index colonoscopy finding of no adenoma, in 4.6% vs 7.0% ( P = 0.03) after a finding of nonadvanced adenoma (NAA), and in 7.9% vs 11.7% ( P = 0.06) after a finding of advanced adenoma (AA), respectively. Compared with the 50–59 years group, the 40–49 years group had a lower risk of metachronous AN when no adenoma was detected on index colonoscopy (hazard ratio [HR] 0.58; 95% confidence interval [CI] 0.39–0.83) and no difference when NAA (HR 0.84; 95% CI 0.54–1.24) or AA (HR 0.83; 95% CI 0.51–1.31) was detected. DISCUSSION: Compared with patients aged 50–59 years, patients aged 40–49 years may have a lower risk of developing metachronous AN when no adenoma is detected on index colonoscopy and a similar risk when NAA or AA is detected. These data suggest current surveillance colonoscopy guidelines may be applicable to patients aged 40–49 years who undergo colonoscopy.